Seasonal biology of malaria vectors in South Africa - Burke, Ashley Morgan (My University, 2020)
Residual malaria transmission refers to all forms of transmission beyond the reach of current control measures. Identifying the entomological drivers of residual transmission is a central component of South Africa’s agenda to interrupt local transmission and to subsequently prevent re-establishment of transmission. This study aimed to 1) evaluate and compare the efficiency of different mosquito collection methods for routine surveillance, 2) determine the seasonal Anopheles assemblage within two malaria-affected regions, and 3) investigate winter dormancy in malaria vector mosquitoes. The merits of passive mosquito shelters (traditional clay pots and modified plastic buckets), used both indoors and outdoors, were assessed in parallel with active methods (human landing catches and CO2 -baited nets) in two malaria affected villages. Passive vector surveillance was conducted weekly and active surveillance conducted monthly. The species of all Anopheles collected was determined using morphological keys and appropriate polymerase chain reaction (PCR) protocols. Every female mosquito was screened for Plasmodium falciparum circumsporozoite protein (CSP). The metabolic rate of wild anophelines, determined by CO2 production during closed system respirometry, was measured. The effect of manipulated photoperiod on the metabolic rate of colonized An. arabiensis mosquitoes was determined by laboratory-based experiments. The outdoor clay pots accrued significantly more wild Anopheles than the plastic buckets and showed productivity alike to the active methods thus showing useful for routine vector surveillance. Changes in local population density of known vector and non-vector species was consistent with seasonal rainfall patterns. Malaria parasite screening of all females collected gave the first ever account of P. falciparum CSP-positive An. vaneedeni and An. parensis females in the wild. Although now considered secondary vectors, their role in malaria transmission in South Africa is likely minimal owing to their strong zoophilic tendency. There were no significant seasonal disparities in metabolic rate data obtained from wild-caught Anopheles nor amongst colonized An. arabiensis placed under simulated seasonal photoperiod conditions. The occurrence of vector species alongside malaria incidence throughout the dry season suggests that local vector populations do not enter a dormant phase in the adult stage. Due to the decrease in populations during winter leading to reduced malaria transmission, the study recommended control by winter larviciding of known breeding sites, which now forms part of South Africa’s malaria vector control and elimination strategy for the period 2019 – 2023
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2020